José Martí: the defeat of the radical intellectual on the scene of colonial capitalism: José Martí: the defeat of the radical intellectual on the scene of colonial capitalism (Élisée - Revista de Geografia da UEG, 2021)
This article analyzes the political and intellectual trajectory of Cuban José Martí (1853-1895). The research seeks to observe to what extent the outstanding revolutionary can be considered a collapsed intellectual from a political and institutional point of view, having as protagonists of this defeat the representative forces of “colonial capitalism” in Latin America. We defend the thesis that the defeat represents the continuity of Spanish colonialism, manifested through other forms of oppression present in nineteenth-century America, such as the imperialist neocolonialism of the United States. The temporal and spatial approach emphasizes Cuba from the mid-nineteenth century, having as theoretical framework the primary sources of martian writings, highlighting the Complete Works, among other intellectuals specialized in the studies of his work.
Keywords: José Martí; Cuba; Intelectual.